Exploring the nexus between MYH9 and tumors: novel insights and new therapeutic opportunities - Gou, Zixuan; Zhang, Difei; Cao, Hongliang; Li, Yao; Li, Yunkuo; Zhao, Zijian; Wang, Ye; Wang, Yishu; Zhou, Honglan (Frontiers in Cell and Developmental Biology, 2024)
The myosin heavy chain 9 (MYH9) gene, located on human chromosome 22, encodes non-muscle myosin heavy chain IIA (NM IIA). This protein is essential to various cellular events, such as generating intracellular chemomechanical force and facilitating the movement of the actin cytoskeleton. Mutations associated with thrombocytopenia in autosomal dominant diseases first highlighted the significance of the MYH9 gene. In recent years, numerous studies have demonstrated the pivotal roles of MYH9 in various cancers. However, its effects on cancer are intricate and not fully comprehended. Furthermore, the elevated expression of MYH9 in certain malignancies suggests its potential as a target for tumor therapy. Nonetheless, there is a paucity of literature summarizing MYH9’s role in tumors and the therapeutic strategies centered on it, necessitating a systematic analysis. This paper comprehensively reviews and analyzes the pertinent literature in this domain, elucidating the fundamental structural characteristics, biological functions, and the nexus between MYH9 and tumors. The mechanisms through which MYH9 contributes to tumor development and its multifaceted roles in the tumorigenic process are also explored. Additionally, we discuss the relationship between MYH9-related diseases (MYH9-RD) and tumors and also summarize tumor therapeutic approaches targeting MYH9. The potential clinical applications of studying the MYH9 gene include improving early diagnosis, clinical staging, and prognosis of tumors. This paper is anticipated to provide novel insights for tumor therapy.